Chromosomal position of rearranging gene segments influences allelic exclusion in transgenic mice. - Costa, T E (1992)
Formation of a complete immunoglobulin heavy-chain transcription unit involves the ordered rearrangement of variable (V), diversity (D), and joining (J) region gene segments. In antibody-producing cells, this process is regulated such that only one of two antibody genes is expressed. Experiments with transgenic mice suggest that this mechanism, known as allelic exclusion, is mediated through the membrane-bound form of the immunoglobulin heavy chain. However, in all transgenic lines produced to date exclusion of the endogenous genes by the transgene is incomplete. To characterize the molecular basis for this escape from regulation, we have examined the rearrangements of endogenous immunoglobulin heavy-chain genes. We find that a transgene that encodes the membrane-bound form of human IgM efficiently inhibits rearrangements of endogenous gene segments located at the 5' end of the heavy-chain locus. However, recombining elements found at the 3' end of the locus escape and continue to undergo recombination. A transgene that encodes the secreted form of the same immunoglobulin protein has no effect on recombination, regardless of position of the recombining segment in the chromosome. These results have important implications for our understanding of the control of allelic exclusion.